ELECTRO-PHOTOMETRY OF SATELLITES IN UZHGOROD BEGINS FROM ODESSA - Epishev, V. P.; Motrunich, Y. M.; Motrunich, I. I.; Naubauer, I. F. (Одеські астрономічні публікації, 2017)
The contribution of photometric observations of satellites in solutions of many scientifically applied tasks is considered. The role of Odessa's astrophysics is specially showed in creation of this method in Laboratory of space researches of the Uzhgorod National University.